KONDUSIFITAS KEHIDUPAN BERAGAMA KAUM EKSPATRIAT INDONESIA DI KOREA SELATAN - Sonezza Ladyanna (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2012)
A Good cooperation intergovernmental has increased the number of Indonesian expatriates in South Korea. The majority among the expatriates are Muslims. In this article, described the conduciveness of religious life ofIndonesian Muslim expatriates in South Korea. The study was conducted withqualitative and comparative methods. The data analysis showed that the Muslim expatriates in South Korea had the efforts and challenges to implement the values of religion in order to become religious people in their new environment because the atmosphere is quite different from their home country.